WEBSITE APPLICATIONS PASKIBRA SMA NEGERI 66 JAKARTA USE JOOMLA - Rafi Rasmika; Diyah Ruri Irawati, SKom, MMSI Diyah Ruri Irawati, SKom, MMSI (Jurnal Sistem Informasi, 2010)
SMA 66 Jakarta paskibra website is a website created to provide information to usersin order to facilitate in identifying paskibra SMA 66 Jakarta.Website Creation Application SMA 66 Jakarta paskibra this using Joomla 1.0. JoomlaCMS is based on open source CMS with a rather large number of users. Joomla CMSis so easy in use and has a very attractive appearance. So that can be expected toattract more users in the know paskibra SMA 66 Jakarta.